Political Dynamics Of Islamic Education In Indonesia: A Systematic Review (2004–2024) - Wahyudin, Aji; Abidin, Munirul; Raharjo, Mudjia (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
Various literature often appears discussions about the politics of Islamic education in Indonesia, but they are rarely used as a theoretical basis because this phenomenon is dynamic. This study aims to Identify the study of the political area of Islamic education, we focus on the trend of the study span of years (2004-2024).  To achieve the objectives of this study, we used a type of SLR methodology with a qualitative approach. First, we formulated a research question by focusing on two RQs, then we searched the literature through "Google Scholar" and "ScienceDirect". Second, build search terms by focusing on six keywords. Third, conducting the selection and evaluation of studies with the SINTA, SCOPUS, DOAJ, Proceedings International indexes. We acquired 21 books and 45 relevant article documents. Fourth, carry out analysis and synthesis through the "Publish or Perish" (PoP) and "VOSviever" applications. Then we conduct content analysis as the main findings. Fifth, report the results. We adopted a systematic approach to report findings on the politics of Islamic education. This study encourages the integration of Islamic values in education policies to strengthen students' character, improve the competence of teachers, and ensure equitable access to quality education. This study can be the basis for making education policy strategies that are relevant to the socio-cultural context of the pluralistic Indonesian society. By prioritizing a holistic approach, Islamic education policies contribute to the development of superior human resources and sustainable community development